IMPLEMENTASI SANDWICH GRAPHIC ORGANIZER UNTUK MENINGKATKAN KEMAMPUAN MENULIS ESEI MAHASISWA SEMESTER III - Lulus Irawati; Sri Lestari; Tri Wahyuni (IKIP PGRI MADIUN, 2014)
Orientation:Using media is used to improve students' cerativity and ability in writing that help students in process of prewriting, especially outlining in brainstorming students' idea. There are some steps that must students do in using sandwich graphic organizer: (1) reading article that related with topic, (2) listing and clustering based on data, (3) outlining by using sandwich graphic organizer map, (4) writing phase, (5) editing phase, (6) revising phase, (7) evaluating. Research purpose: This research is aimed at finding out whether: (1) using Sndwich Graphic Organizer improved students' ability in writing essay, (2) The strengthen and weaknesses of using sandwich graphic organizer. Sandwich graphic organizer is a media to help students in writing essay. Research design: The research method was action research. Technique of collecting data was kuantitative data; writing test result and quessionaire, and documentation of the writing process and learning. Technique of analisys of data were: Comparative Method and statistic descriptive. Main Finding: The research findings show that: (1) the ability of students in writing argumentative essay improve. It can be seen by students result score in postest of cycle 2 from 75 in cycle 1 to 79 in cycle 2; (2) the strengthen of using sandwich graphic organizer were: (a) students were active in process of teaching and learning, (b)sandwichhelped students in making outlining, (c) by using sandwich can support students to read many articles. In contrast, the weaknesses of using Sandwich Graphic Organizer were; (a) need much time , (b)some students difficult to fill sandwich pattern.